1995
DOI: 10.1152/ajprenal.1995.268.5.f876
|View full text |Cite
|
Sign up to set email alerts
|

Calcium activation mechanisms in the renal microvascular response to extracellular ATP

Abstract: Previous studies have suggested a paracrine role for extracellular ATP in the regulation of afferent arteriolar tone. The current study was conducted to determine the dependence of this response on calcium entry mechanisms. Experiments were performed in vitro using the blood-perfused juxtamedullary nephron technique combined with video microscopy. The afferent arteriolar response to alpha, beta-methylene ATP was determined before and after treatment with the calcium channel blockers, diltiazem or felodipine. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
53
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(59 citation statements)
references
References 0 publications
6
53
0
Order By: Relevance
“…ATP-mediated afferent arteriolar vasoconstriction is largely dependent on the influx of extracellular Ca 2ϩ and the sustained vasoconstriction is maintained by Ca 2ϩ influx through voltage-dependent L-type Ca 2ϩ channels (Inscho et al, 1995(Inscho et al, , 1999aNavar et al, 1996;Inscho and Cook, 2002). P2 receptor activation results in the release of arachidonic acid from membrane phospholipids in glomerular mesangial cells and rat astrocytes (Pfeilschifter, 1990; Schulze-Lohoff et al, Bolego et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ATP-mediated afferent arteriolar vasoconstriction is largely dependent on the influx of extracellular Ca 2ϩ and the sustained vasoconstriction is maintained by Ca 2ϩ influx through voltage-dependent L-type Ca 2ϩ channels (Inscho et al, 1995(Inscho et al, , 1999aNavar et al, 1996;Inscho and Cook, 2002). P2 receptor activation results in the release of arachidonic acid from membrane phospholipids in glomerular mesangial cells and rat astrocytes (Pfeilschifter, 1990; Schulze-Lohoff et al, Bolego et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…ATP induces vasoconstriction by activating P2 receptors on preglomerular microvascular smooth muscle cells (Inscho et al, 1995(Inscho et al, , 1998Eltze and Ullrich, 1996). This vasoconstriction seems to depend on activation of P2X and P2Y receptors.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The L-type calcium channel inhibitor, diltiazem, abolished the afferent arteriolar constriction elicited by 12(S)-HETE. Diltiazem was administered at a dose that completely blocks KCl-mediated afferent arteriolar constriction (35). These initial functional studies suggest that L-type calcium channel activation contributes to the 12(S)-HETE-mediated constrictor response.…”
Section: Discussionmentioning
confidence: 99%
“…In the isolated juxtamedullary nephron preparation, ATP induces an initial vasoconstriction of the afferent arterioles (Inscho et al, 1995;Inscho et al,1996) that wanes and finally remains a residual vasoconstriction, as observed in "in vivo" studies; the blockade of adenosine receptors increases the ATP-mediated vasoconstriction. The ATP vasoconstrictor effect was maintained during the blockade of nitric oxide, supporting the notion that stimulation of P2Yreceptors induce an initial vasoconstriction that is counterbalanced by a later NO release, resulting in a transient vasoconstriction induced by ATP (Inscho et al, 1994).…”
Section: Effect Of Purinergic Receptors Activation On the Regulation mentioning
confidence: 79%